(untitled) (Vietnam Journal of Community Medicine, 2024)
Background: The elderly people are still among the most vulnerable and poorest populations. Therefore, the quality of life among elderly people need more attention from family and society. Objective: Analysis of some related factors to the quality of life among elderly people at Van An commune, Chi Linh city, Hai Duong and Vinh Tien commune, Kim Boi district, Hoa Binh, in 2020- 2021. Methods: Cross-sectional study. The study collected information from 622 elderly people in 2 communes of Hoa Binh and Hai Duong provinces through standardized WHOQoL-100 questionnaires in Vietnam. The questionnaires included 75 questions with 6 concepts of quality of life. Data were entered by Epidata 3.1 and analyzed by SPSS 20.0. Results: 85.2% of the elderly had average quality of life, 9.5% had low quality of life and 5.3% had good quality of life. Factors contributing to the change in quality of life of the elderly: ethnicity (10.17%), age (4.09%), education level (9.60%), marital status (7.33%), people living with, health status (12.79%), previous occupation (6.89%), occupation (0.88%) and contributing to 30.7% of events changes in the average quality of life score of the elderly. The factor of chronic disease contributes the greatest weight to the change in quality of life of the elderly (12.97%). Conclusion: Factors: ethnicity, education level, age group, marital status, person living with, health status in the past month, chronic disease and occupation are closely related drastically changes the quality of life of the elderly.